2022
DOI: 10.1136/bmjopen-2021-056856
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ experiences regarding neonatal care during the COVID-19 pandemic: country-specific findings of a multinational survey

Abstract: ObjectivesThe COVID-19 pandemic has disrupted healthcare systems, challenging neonatal care provision globally. Curtailed visitation policies are known to negatively affect the medical and emotional care of sick, preterm and low birth weight infants, compromising the achievement of the 2030 Development Agenda. Focusing on infant and family-centred developmental care (IFCDC), we explored parents’ experiences of the disruptions affecting newborns in need of special or intensive care during the first year of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 59 publications
1
8
1
Order By: Relevance
“…The results we found were similar to those described by others 19,38,39 , who defined similar themes: less family involvement, reduced emotional and physical support for women, compromised standards of care, increased exposure to medically unjustified cesarean section, and staff overwhelmed by rapidly changing guidelines and enhanced infection prevention measures 40 , as well as a decrease in respectful care due to fears surrounding COVID-19 transmission 2,38,41 . At the same time, interviewees reported that facilities that were known for providing more motherfriendly and baby-friendly care made great efforts to maintain that level of quality, sometimes at considerable staff effort, whilst otherwise less friendly facilities more rapidly downgraded their services.…”
Section: Postnatal Maternal Mental and Physical Healthsupporting
confidence: 87%
See 1 more Smart Citation
“…The results we found were similar to those described by others 19,38,39 , who defined similar themes: less family involvement, reduced emotional and physical support for women, compromised standards of care, increased exposure to medically unjustified cesarean section, and staff overwhelmed by rapidly changing guidelines and enhanced infection prevention measures 40 , as well as a decrease in respectful care due to fears surrounding COVID-19 transmission 2,38,41 . At the same time, interviewees reported that facilities that were known for providing more motherfriendly and baby-friendly care made great efforts to maintain that level of quality, sometimes at considerable staff effort, whilst otherwise less friendly facilities more rapidly downgraded their services.…”
Section: Postnatal Maternal Mental and Physical Healthsupporting
confidence: 87%
“…Although some authors have reported on parents' experiences in neonatal care 11,19 , to our knowledge, no other published research has used a human-rightsbased approach to survey national pandemic-related changes to care for pregnant and birthing women from the perspective of parents' organizations. Organizations representing patients overall, or specific patient groups (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some mothers do not even know the faces of their babies. In Turkey and China, the highest rates of access restrictions due to the pandemic were reported where no one was permitted to visit newborns ( Kostenzer et al, 2022 ). Strict access policies create challenges for parents and health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Before the pandemic, these countries struggled with limited resources, inadequate healthcare infrastructure, and high maternal and neonatal mortality rates. The pandemic has further exacerbated these challenges, disrupting essential neonatal care services (16).…”
Section: The Impact Of Covid-19 Neonatal Services In Developing Count...mentioning
confidence: 99%